INTERPRETAÇÃO DO ESTADO NUTRICIONAL DE SOJA PELO DRIS NO MATO GROSSO DO SUL - Maeda, Shizuo (Scientia Agraria, 2003)
Methods for crop nutritional diagnosis are important tools to support decisions during the process of soil fertility management. Such procedures allow farmers to increase their chances to obtain profitability and to promote greater environmental sustainability of agricultural systems. For that purpose, particularly in Brazil, soil and leaf analysis have been the mostly used methods. However, it is well known that the resultant interpretation done in an isolated way for each nutrient by either the critical levels or the concentration ranges criteria are difficult to be organized under a hierarchy of limitations and are affected by several factors such as variety , tissue age, climate and soil properties, points which constitute restrictions for the validity and quality of recommendations based on them. In order to overcome such limitations some authors have proposed an alternative interpretation method, the Diagnosis and Recommendation Integrated System (DRIS), considered less susceptible but yet influenced by some factors in its discriminatory ability and efficiency of diagnosing plant nutrition status, and thus requiring the development of reference values for its regional application. The aim of this work was to characterize the nutritional status of soybean crops cultivated during the agricultural year of 2000/2001 in the southern portion of the state of Mato Grosso do Sul, Brazil, in order to allow comparisons between the leaf nutrient concentration ranges criteria and the DRIS. For that purpose soil and soybean grain and leaves were sampled in commercial areas, always from same sites. The soil was taken during V1 until V4 stage period at 5 depths (0-5, 5-10, 10-20, 0-20, and 20-40 cm), and the leaves were sampled during the R 1 stage. Regional reference values based on the leaf samples were established and validated by comparing DRIS interpretation with the visual diagnosis method. The efficacy and the ability to discriminate and to order nutritional problems were better for DRIS than for the other tested methods. This was demonstrated when data from a leaf sample presenting a classical Mn visual deficiency symptom led DRIS to rank Mn as the most limiting nutrient. Besides, for this case, data interpretation by the concentration range criteria gave N, Cu and P as the most deficient nutrients in the leaves, and Zn, K and P in the soil. On the other hand, the difference between outputs given by DRIS based on published values and DRIS based on. regional values suggests that refinement of reference values may be beneficial when an improvement in DRIS accuracy is required.